Prediction Modelling Of Power And Torque In End-Milling - K., Kadirgama; M. M., Noor; M. M., Rahman; R. A., Bakar; M. S. M., Sani (2009)
This paper presents the development of mathematical models for torque and power in milling 618 stainless steel using coated carbides cutting tool. Response surface method was use to predict the effect of power and torque in the end-milling. From the model, the relationship between the manufacturing process factors including the cutting speed, feed rate, axial depth and radial depth with the responses such as torque and power can be developed. Beside the relationship, the effect of the factors can be investigated from the equation developed. It can seen that the torque increases with decreases of cutting speed while increase of the feed rate, axial depth and radial depth. The acquired results also shown that the power increases with the increases of cutting speed, feed rate, axial depth and radial depth .It can be found that the second order is more accurate based on the variance analysis and the predicted value is closely match with the experimental result. Third- and fourth- order model generated for both response to investigate the 3- and 4-way interaction between the factors. The third and fourth order model shows that 3- and 4-way interaction found less significant for the variables.